Transforming community-based tourism management toward a sustainable cultural destination: A case study of Osing Kemiren tourism village, Indonesia - Widowati, Sri; Suharsono, Hamong (Journal of Commerce, Management, and Tourism Studies, 2026)
This study aims to analyze the factors influencing the sustainability of Kemiren Tourism Village, Banyuwangi, Indonesia, by examining the effects of community participation, community-based tourism, local cultural preservation, economic benefits, social benefits, tourism village governance, and local wisdom. The study employed a quantitative explanatory approach involving 347 respondents from the Kemiren community. Data were collected through a structured questionnaire consisting of 25 indicators measured using a five-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that community participation has a positive and significant effect on tourism village sustainability (β = 0.241, t = 5.130, p < 0.001). Local cultural preservation also has a positive and significant effect (β = 0.191, t = 4.016, p < 0.001), as do economic benefits (β = 0.134, t = 2.527, p = 0.012) and local wisdom (β = 0.230, t = 5.062, p < 0.001). In contrast, community-based tourism (β = 0.058, t = 1.150, p = 0.250), social benefits (β = 0.016, t = 0.367, p = 0.714), and tourism village governance (β = 0.078, t = 1.534, p = 0.125) do not have significant direct effects on tourism village sustainability. The structural model produces an R² value of 0.459, indicating that the proposed constructs explain 45.9% of the variance in tourism village sustainability. The findings demonstrate that strengthening community participation, preserving local culture, increasing economic benefits, and maintaining local wisdom are essential priorities for achieving sustainable tourism village development in Kemiren. The study provides empirical implications for local governments and tourism village managers in developing community-centered and culturally grounded sustainability strategies.